PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS NATURALIS INTELLIGENCE TERHADAP CURIOSITY DAN SCIENTIFIC LITERACY DI SEKOLAH DASAR - Amelia Putri; Hilman Hilmawan; Yoesrina Novia Vini Syafitri; Nisa Saptania; Ranti Agustiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school students’ curiosity and scientific literacy still need to be improved through the implementation of learning models that actively engage students in the learning process. This study aims to determine the effect of the Naturalistic Intelligence-based Problem-Based Learning (PBL) model on elementary school students’ curiosity and scientific literacy. This is a quantitative study using a quasi-experimental method with a non-equivalent control group design. The research subjects in this study were fifth-grade students at SDN Sukaraja 1, consisting of 36 students in the experimental class and 34 students in the control class. The research instruments used were a questionnaire to measure curiosity and a test to measure scientific literacy. Data analysis was conducted using descriptive statistics, prerequisite tests—including normality and homogeneity tests—and hypothesis testing with the aid of IBM SPSS Statistics version 26. The results showed that the significance values for the curiosity variable were 0.000 and for scientific literacy were 0.000, meaning both were < 0.05. Based on these results, it can be concluded that the Problem-Based Learning (PBL) model based on Naturalist Intelligence has an effect on the curiosity and scientific literacy of elementary school students.